TO ΕΡΓΟ ΤΟΥ ΜΕΘΟΔΙΟΥ ΑΝΘΡΑΚΙΤΗ ΚΑΙ ΤΑ ΠΟΛΙΤΙΚΟΕΚΚΛΗΣΙΑΣΤΙΚΑ ΣΧΕΔΙΑ ΤΟΥ ΜΕΛΕΤΙΟΥ ΤΥΠΑΛΔΟΥ - ΤΣΑΚΙΡΗΣ, ΒΑΣΙΛΕΙΟΣ (Eoa kai Esperia, 2013)
The three pastoral manuals authored by Methodios Anthrakites, Θεωρίαι Χριστιανικαί, Ἐπίσκεψις Πνευματικοῦ πρὸς ἀσθενῆ and Βοσκὸς λογικῶν προβάτων, that draw heavily on the works of the Jesuit preacher P. Segneri and other Italian sources, and directly connected to the current developments in the Greek Orthodox community of Venice in the late seventeenth c. The communty’s metropolitan bishop Meletios Typaldos pursued the ambitious goal of uniting all orthodox communities in Venetian territory under his own See, ascending to the ecumenical throne of Constantinople and, finally, subduing all orthodox churches to the Vatican. Part of this complex plan was also the broad diffusion of manuals of pastoral theology, intended both to advertise Typaldos’ active care for his fold and set a limit to the arbitrariness of the localclergy. Anthrakites, a close collaborator of Typaldos, was fully qualified to undertake writing these manuals. A close comparison between a memorandum on the state of the Greek Church under Venetian dominion, written by Typaldos for the Provveditore of Peloponnesos, Polo Nani, and the three aforementioned manuals, demonstrates their close interrelationship and sheds light on the different ambitions pursued by bishop Meletios and by Methodios Anthrakites.